"PROFESSIONAL SELF-IMAGE" AS A COMPONENT OF THE PROFESSIONAL IDENTITY OF THE FUTURE SPECIALIST - Patrul, Mariia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The content of the article analyzes and summarizes scientific research on issues of professional identity. The scientific positions of domestic and foreign scientists regarding the structural components and features of the formation of professional identity are outlined. The concept of the image "Professional self" is singled out as a constituent phenomenon of professional identity. The purpose of the study is the theoretical substantiation of the concept of the image "I-professional" as a component of the professional identity of future specialists. The goal is produced by the need to prepare a competitive future specialist, where a special place is occupied by the aspect of the formation of the "I-professional" image - the awareness and evaluation of oneself as a representative of a certain profession, which corresponds to a set of professionally significant qualities, which subsequently affects the formation of a professional identity, which is essential an aspect of a person's self-knowledge in the relevant field of activity. The research procedure involved the use of analysis, synthesis, generalization, bibliographic and comparative methods in order to identify the fundamental essential characteristics of the phenomenon under study. At the level of such methodological systematicity, the constituent components of professional identity are singled out: communicative, emotional-volitional and empathic. Attention is focused on the main system-forming phenomenon of professional identity - the image of "I-professional". It is problematized that the formation of the phenomenon of the "I-professional" image is directly related to the content and requirements of the future profession. The result of the study was the ascertainment of the significance of the phenomenon of the professional identity of future specialists under investigation, which is formed on the basis of the positive formation of the image of the "I-professional", which, in turn, is produced on the basis of the comparison of the image of the profession with the image of the "I" of the student, and the awareness of one's identity is formed with the chosen profession, a positive attitude towards oneself as a subject of real educational and professional activity and future professional and industrial activity is formed. The conclusions summarize the phenomenological significance of the "I-professional" image in the formation of the professional identity of the future specialist. It is concluded that the process of becoming a professional, the success of mastering professional activities, and entering a professional community depends on the level of formation of the "I-professional" image. A conclusion was made about the specifics of the formation of the "I-professional" image related to the content and requirements of the future profession